THE INFLUENCE OF CIVIC EDUCATION TEACHER’S AFFECTION TOWARDS STUDENT’S CHARACTER AND STUDENT’S LEARNING RESULT AT SMA PERINTIS 2 BANDAR LAMPUNG 2011/2012 - yuni martha nainggolan; Adelina Hasyim; Mohammad Mona Adha (Jurnal Kultur Demokrasi, 2012)
This research was intended to explain the influence of civic education teacher’s affection towards student’s character and student’s learning result at SMA Perintis 2 Bandar Lampung. In this research, the researcher used descriptive quantitative method. The sample of this research was taken as 10% from 479 the number of students at SMA Perintis 2 Bandar Lampung 2011/2012 and the researcher got 48 students as the sample of this research. The data collecting technique in this research were questionnaires, attitude scales and test. Based on the calculation of data analysis, the result showed that there was positive influence and there was significant between civic education teacher’s affection towards student’s character, the higher of civic education teacher’s affection so the higher of student’s character, e.g. instill a sense of mutual help and respect to the students, as well as the lifestyle of a good teacher could increase the student’s character in their daily lives. And also there was positive influence and there was significant between civic education teacher’s affection towards students’ learning result, the higher influence of civic education teacher’s affection, the higher of student’s learning result, e.g. the affection of the teacher could increase students’ enthusiasm in understanding the question and the task of the material with confidence and the students were active in discussion in whole of class.Keywords: affection, civic education, student’s character, learning result.